Our experience with 3D CT - Pach, Miroslav; Ditmar, Rudolf; Heřman, Miroslav (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1999)
The authors present the results of 9-year work with 3D CT in orthopaedics and musculoskeletal traumatology. In the years 1990-1998, the method was used in the examination of 59 patients (27 males, 20 females, and 12 children). The place of 3D CT in clarifying areas of complex musculoskeletal anatomy for operative treatment is discussed and presented as a contribution to the indication conference. According to the authors' experience, in many cases 3D CT increases the quality of diagnostics. Most of all, it helps the surgeon in operation planning. 3D reconstructions are particularly valuable in proximal humerus fractures, spine fractures and tumours, acetabulum fractures, as well as in conditions after hip dysplasia, LCPD and coxa vara adolescent.
Keywords: dospělí; fraktury kostí; Female; dítě; Adult; ženské pohlaví; Tomography, X-Ray Computed; nemoci kostí; ortopedie; lidé; Fractures, Bone; Bone Diseases; retrospektivní studie; Male; počítačové zpracování obrazu; počítačová rentgenová tomografie; Child; mužské pohlaví; Retrospective Studies; Orthopedics; Image Processing, Computer-Assisted; Humans